Health, nutrition and hydration status of Indonesian workers: a preliminary study in two different environmental settings (Faculty of Medicine Universitas Indonesia, 2014)
Background: Hydration status in the working environment of hot and conveniently cool may influence the health status of workers, including their hydration status. This study aimed to determine the health, nutrition and hydration status of workers in two different working environment, i.e. hot and conveniently cool environment. Methods: A cross-sectional comparative study was done on apparently healthy male subjects, age 25-45 years. Two groups of factory workers consisted of 39 subjects working in environment exposed directly to heat and the other doing administrative work in cool environment. Data on their health status (physical examination), weight, height, waist circumference, fat body composition, laboratory result, were collected. The data was presented as average value and proportion; statistical analysis with unpaired-t (Mann-Whitney test) and chi-square test was used. Results: Subjects working in a hot environment were more prone to dehydration in comparison to their counterparts, as was shown by significantly higher values of several hydration status biomarkers: hemoglobin (15.6 vs 14.8 g/dL, p = 0.017), hematocrit (46 vs 44.5%, p = 0.040), blood viscosity (23 vs 12 mEq/L, p < 0.001), and blood sodium concentration (140 vs 138 mEq/L, p < 0.001). In contrast, subjects working in a conveniently cool environment who did more administrative tasks were physically less active, had significantly lower HDL-cholesterol level (43 vs 52.1 mg/dL, p = 0.005), higher body and visceral fat compositions (21.6 vs 17.6%, p = 0.008, and 10 vs 8%, p = 0.015, respectively) compared to their counterparts. Conclusion: Workers in hot and cool working environment are prone to nutrition- and health problems as well as dehydration, suggesting special attention to the provision of timely drinking water, and physical activity during working time.